(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Todays’ world is highly competitive than ever before. New technologies, machines, human beings are getting increasingly productive to sustain and survive in the world. In todays’ globalized world in India’s position as manufacturing force is getting noticed. Hence the scale of efficiency has become global benchmark.Every manufacturing facility wants production system and equipment and operated in reliably. Everyone wants production system or process to work without breakdown and produce consistent quality of products or to operate efficiently and perfectly. There is no ideal world, no physical asset has operated flawlessly forever.Maintenance of engineering equipment in the field has been a challenge due to size, cost, complexity and competition. Although progress has been made in maintaining equipments in reasonable manner. The professionals are developed specializing in this area as per market driven in a manufacturing or process industry or service suppliers etc. Thus, there is a definite need for effective asset maintenance practices that will positively influence critical success factors such as safety, product quality, speed of innovation, price, profitability, technical obsolesce, and reliable delivery.In organization where there are surprises and breakdowns, the quality and productivity losses are high.The huge opportunity to reduce the manufacturing cost especially in a plant where there is a capacity crunch is not appreciated by all.” Zero breakdown “is not just a buzz word but reality today and this is zero breakdown concept can bring about huge savings in manufacturing costs. In industrial world the awareness of important function is rapidly increasing. The science of maintenance is ever developing, and it is important to know the latest developments in the field of maintenance in order to sustain the results.